PERGESERAN BAHASA PADA MASYARAKAT GENERASI KEDUA DARI NUSA TENGGARA TIMUR DI DRIYOREJO - Haryono, Aura Hilda; Hadiutomo, Dwi Anggoro (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
Migration is a response to changes in the environment where people live, including those from East Nusa Tenggara who have decided to move to Gresik. Like others who relocate to a new place, they must adapt to their new environment, especially with the language. This inevitably leads to language shift. Based on the explanation above, this study aims to analyze the forms of language shift and the factors causing language shift among the second generation of East Nusa Tenggara migrants who have moved to Driyorejo, Gresik. In this research, the author collected data through observations and interviews with participants. The author observed participants in school, home, and through online. The results indicate that the forms of language shift found in the second generation from East Nusa Tenggara are partial language shift observed in three families and permanent language shift found in two families. Furthermore, four factors contribute to the language shift among the second-generation East Nusa Tenggara community in Gresik: social factors, demographic factors, attitudes and values, and political policies.